You're never alone with ALIN - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Arid Lands Information Network (ALIN) is perhaps best known for its Baobab journal, but it deserves wider recognition as a continental network of development workers. Launched in 1988, as a Northern and sometimes questioned initiative, ALIN is...